2006
DOI: 10.1590/s1415-43662006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação do feijoeiro comum (Phaseolus vulgaris L.) à seca

Abstract: RESUMORealizou-se este trabalho tendo em vista o propósito de se estudar a adaptação de genótipos de feijoeiro comum (Phaseolus vulgaris L.) à seca, como suporte a programas de melhoramento que visem à criação de cultivares para regiões sujeitas a deficiência hídrica, mediante a avaliação do potencial da água nas folhas e da resistência difusiva estomática. Adicionalmente avaliou-se a técnica de medição da temperatura do dossel pela termometria de infravermelho para inferir o estado hídrico da planta. Os genót… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
0
16
0
11
Order By: Relevance
“…Behavior differences were found only under drought, where the leaf Ψ w varied between -0.73 and -1.20 MPa. Guimarães et al (2006) registered minimum values of 0.97 and -1. 07 MPa for leaf Ψ w evaluated in the period of maximum intensity of solar radiation in two bean cultivars subjected to water stress during the reproductive period.…”
Section: Resultsmentioning
confidence: 99%
“…Behavior differences were found only under drought, where the leaf Ψ w varied between -0.73 and -1.20 MPa. Guimarães et al (2006) registered minimum values of 0.97 and -1. 07 MPa for leaf Ψ w evaluated in the period of maximum intensity of solar radiation in two bean cultivars subjected to water stress during the reproductive period.…”
Section: Resultsmentioning
confidence: 99%
“…FAO (2000) reported many cases where DI was a beneficial impact on water savings. In SA, deficit irrigation techniques has been investigated for olives (Sellés et al, 2006), grapevine (Ferreyra et al, 2003), Chilean tomato (Maldonado et al, 2003) in Chile; maize (Bergamaschi et al, 2006), sugarcane , irrigated coffee (Fernandes et al, 2000), sorghum (Peiter and Carlesso, 1996), beans (Phaseolus vulgaris) (Calvache et al, 1997;Guimarães et al, 2006), garlic (Macêdo et al, 2006), watermelon (Citrullus lanatus) (Andrade Júnior et al, 2001) in Brazil; quinoa in Bolivia (Geerts et al, 2006); sugar cane in Argentina (Romero et al, 2006).…”
Section: Deficit Irrigation As a Water Saving Practicementioning
confidence: 99%
“…Guimarães et al (2006) reported that a water-deficit tolerant common bean cultivar, subjected to water-stress conditions, showed higher leaf-water potential and lower stomatal diffusive resistances than a susceptible cultivar.…”
Section: Introductionmentioning
confidence: 99%